(untitled) (Bangladesh Journal of Plant Taxonomy, 2011)
Three species belonging to Sterculiaceae, namely Guazuma ulmifolia Lam., Helicteres viscida Bl. and Sterculia urens Roxb. are recorded here for the first time for Bangladesh. Of these, the genus Guazuma is also a new generic record for the country. Updated nomenclature, important synonyms, description, ecology and geographical distribution are provided for each species. Keywords: Sterculiaceae; New records; Guazuma ulmifolia; Helicteres viscida; Sterculia urens; Bangladesh. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9301 Bangladesh J. Plant Taxon. 18(2): 153-157, 2011 (December)